2020
DOI: 10.21294/1814-4861-2020-19-1-50-56
|View full text |Cite
|
Sign up to set email alerts
|

Radical Prostatectomy and Robotic Radiosurgery as Treatment Options for Localized Prostate Cancer

Abstract: Аннотация Цель исследования-сравнить показатели непосредственных, ближайших и отдаленных результатов лечения после радикальной простатэктомии и роботизированной радиохирургии у пациентов с локализованным раком предстательной железы. Материал и методы. В исследование включены 2 группы пациентов: первая группа-80 больных, получивших хирургическое лечение (радикальная позадилонная нервосберегающая простатэктомия), вторая группа-102 пациента, которым проведена роботизированная стереотаксическая лучевая терапия на … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…It radiates higher prostate radiation doses, with less emission to the surrounding tissues. Radiation therapy is considered to be an effective intermediate-risk and high-risk prostate cancer treatment when used together with androgen deprivation therapy (ADT) [ 80 ]. It is a suitable therapy for attenuating metastasizing cancer cells.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It radiates higher prostate radiation doses, with less emission to the surrounding tissues. Radiation therapy is considered to be an effective intermediate-risk and high-risk prostate cancer treatment when used together with androgen deprivation therapy (ADT) [ 80 ]. It is a suitable therapy for attenuating metastasizing cancer cells.…”
Section: Methodsmentioning
confidence: 99%
“…Gene expression profiling results have indicated an overexpression in EZH2 mRNA and proteins present in metastatic prostate cancer. Due to the functions of EZH2 involving apoptosis and proliferation, EZH2 is a novel target for prostate cancer [ 80 ].…”
Section: Figurementioning
confidence: 99%
“…It can be used as an alternative to surgery or after surgery to prevent cancer recurrence. External beam radiation therapy delivers precise radiation to prostate tissue, sparing healthy cells, and is considered effective for intermediate-risk and high-risk PCa [53]. However, studies have shown that PCa cells can adapt to radiotherapy, increasing the risk of disease recurrence [54].…”
Section: Current Therapeutic Strategies Used In Prostate Cancermentioning
confidence: 99%